1995
DOI: 10.1016/s1078-5884(05)80055-3
|View full text |Cite
|
Sign up to set email alerts
|

Oral ciprofloxacin versus intravenous cefuroxime as prophylaxis against postoperative infection in vascular surgery: A randomised double-blind, prospective multicentre study

Abstract: The infection rate was similar in the two groups. Thus, oral administration of ciprofloxacin is an attractive, cost-effective and safe alternative to prophylaxis in vascular patients capable of taking oral medication on the day of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…872 A multicenter, randomized, double-blind, prospective trial of 580 patients undergoing arterial procedures involving the groin who received either two doses of ciprofloxacin 750 mg orally or three doses of cefuroxime 1.5 g i.v. on the day of the procedure found an SSI rate of 9.2% (27 patients) and 9.1% (26 patients), respectively, within 30 days of the procedure 889 Although oral ciprofloxacin was shown to be as effective as i.v. cefuroxime, this study did not address concerns about resistance with routine use of fluoroquinolones.…”
Section: Vascular Proceduresmentioning
confidence: 93%
See 1 more Smart Citation
“…872 A multicenter, randomized, double-blind, prospective trial of 580 patients undergoing arterial procedures involving the groin who received either two doses of ciprofloxacin 750 mg orally or three doses of cefuroxime 1.5 g i.v. on the day of the procedure found an SSI rate of 9.2% (27 patients) and 9.1% (26 patients), respectively, within 30 days of the procedure 889 Although oral ciprofloxacin was shown to be as effective as i.v. cefuroxime, this study did not address concerns about resistance with routine use of fluoroquinolones.…”
Section: Vascular Proceduresmentioning
confidence: 93%
“…Prophylactic antimicrobials decrease the rate of infection after procedures involving the lower abdominal vasculature and procedures required to establish dialysis access. The follow-up time for patients with late surgical-site complications was at least once after hospital discharge (not further defined) for most studies, 829,865,871,[885][886][887] at one month, 869,871,888,889 at six months, 872 and at three years. 138 A meta-analysis of 10 randomized controlled trials in patients undergoing peripheral arterial reconstruction with biological or prosthetic graft procedures found an overall consistent reduction in SSIs with systemic antimicrobial prophylaxis compared with placebo (relative risk, 0.25; 95% CI, 0.17-0.38; p < 0.00001).…”
Section: Vascular Proceduresmentioning
confidence: 99%
“…A multicenter, randomized, double-blind, prospective trial of 580 patients undergoing arterial procedures involving the groin who received either two doses of ciprofloxacin 750 mg orally or three doses of cefuroxime 1.5 g i.v. on the day of the procedure found an SSI rate of 9.2% (27 patients) and 9.1% (26 patients), respectively, within 30 d of the procedure [889] Although oral ciprofloxacin was shown to be as effective as i.v. cefuroxime, this study did not address concerns about resistance with routine use of fluoroquinolones [891].…”
Section: Efficacymentioning
confidence: 94%
“…Prophylactic antimicrobials decrease the rate of infection after procedures involving the lower abdominal vasculature and procedures required to establish dialysis access. The follow-up time for patients with late surgical site complications was at least once after hospital discharge (not further defined) for most studies [829,865,871,[885][886][887], at one month [869,871,888,889], at six months [872], and at three years [138].…”
Section: Efficacymentioning
confidence: 99%
“…In other fields, Tuji et al [19] reported that the prophylactic effect of oral tosufloxacin was equivalent to that of intravenous cefotiam after transurethral resection of the prostate. Risberg et al [20] reported that oral ciprofloxacin was as effective as intravenous cefuroxime in peripheral vascular surgery involving the groin. When both methods are compared regarding costeffectiveness, the daily cost of oral levofloxacin at a dose of 100 mg t.d.s.…”
Section: Discussionmentioning
confidence: 99%